2024
DOI: 10.1590/1519-6984.254816
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Aeromonas hydrophila isolates from diseased fishes in district Kasur, Punjab, Pakistan

Abstract: Pakistan is an agricultural country and fisheries play a very important role in the economic development of the country. Different diseases are prevalent in Pakistani fish but information related to the causative agents is not well-known. Keeping in view the significance of bacterial pathogens as the causative agents of multiple fish diseases, the present study was conducted for identification, characterization and analysis of virulence genes of Aeromonas spp. isolated from diseased fishes. A total of fifty fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
0
0
1
Order By: Relevance
“…(P. fluorescens and P. putida) and K. oxytoca wererecovered from naturally infected Nile tilapia in El-Serw aquaculture fish farm of Egypt (Austin and Austin, 2016).The author also reported that the higher number of Aeromonas isolates commonly infect Nile tilapia than Pseudomonas isolates. A study on naturally infected fish in fish farms of district Kasur, Punjab, Pakistan found significantly virulent bacterial pathogens such as A. hydrophila from Nile tilapia (Tooba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(P. fluorescens and P. putida) and K. oxytoca wererecovered from naturally infected Nile tilapia in El-Serw aquaculture fish farm of Egypt (Austin and Austin, 2016).The author also reported that the higher number of Aeromonas isolates commonly infect Nile tilapia than Pseudomonas isolates. A study on naturally infected fish in fish farms of district Kasur, Punjab, Pakistan found significantly virulent bacterial pathogens such as A. hydrophila from Nile tilapia (Tooba et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cacing Tubifex juga menunjukkan variabilitas yang cukup besar dalam kerentanan terhadap parasit Myxobolus sp melalui konsumsi myxospora (Lodh et al, 2011;Richey et al, 2018). Perkembangan dan penggandaan parasit terjadi di antara sel-sel epitel usus cacing Tubifex dan biasanya memakan waktu sekitar 2-3 bulan (Kusdarwati et al, 2017;Mandal et al, 2018;Tooba et al, 2024) sehingga spora triactinomyxon yang ditularkan melalui air (TAMs) dilepaskan ke air bersama kotoran cacing Tubifex. Infeksi pada cacing Tubifex dapat bertahan selama masa hidup cacing Tubifex dan pelepasan TAM dapat terjadi secara berkala selama rentang waktu setidaknya beberapa tahun.…”
Section: Pembahasanunclassified